Ultra-compact low loss polarization insensitive silicon waveguide splitter - Xiao, Zhe (2013)
We observe that the cascaded typical Y junctions will introduce unwanted periodic fringes over the spectrum in practical systems when they link with multimode waveguides. To solve the problem, we design and experimentally demonstrate a wavelength insensitive multimode interferometer (MMI) based 3-dB splitter which has all the merits of Y-splitters such as polarization insensitivity and ultra-compactness. The splitter has a footprint of 1.5 × 1.8 µm2, nearly one order smaller than the previously reported MMI splitters. The measured excess losses for TE and TM modes at telecom wavelength are as low as −0.11 dB and −0.18 dB respectively.